Evaluasi Penerapan Teknologi Informasi E-Learning Pada Kampus Swasta Menggunakan Cobit 4.1 - khairan Marzuki; Apriani Apriani; lalu zazuli azhar mardedi (Jurnal Bumigora Information Technology (BITe), 2019)
An online learning system (e-learning) at private tertiary institutions is built to facilitate lecturers and students in the teaching and learning process. Through the e-learning learning information system students can download course material, send assignments, work on daily and semester exam questions, find out the value of assignments and examinations. Bumigora University has been implementing e-learning since 2017. Thus to determine the usefulness and feasibility of applying the application must be evaluated in accordance with the vision and mission of the institution. In this study the evaluation of the application of e-learning will use the COBIT 4.1 framework with the domain monitoring evaluation. The results of this study determine the level of maturity of the application of e-learning applications today (as-is) and the expected maturity (to-be).